(untitled) - Coulthard, Glen J. (Boston, 2004)
The Advantage Series presents the Feature-Method-Practice approach to computer software applications to today's technology and business students. This series implements an efficient and effective learning model, which enhances critical thinking skills and provides students and faculty with complete application coverage.
Keywords: Sự xử lý văn bản,Word processing,Chương trình word,Microsoft word